An analysis of hazardous waste across different land use zones in Musina Local Municipality, Limpopo Province, South Africa - Nematshavhawe, Happy Andani (My University, 2021)
Hazardous wastes (HW) refer to wastes that may or tend to cause adverse health effects on the ecosystem and human beings. These wastes pose present or potential risks to human health or living organisms, due to the fact that they are: (i) non-degradable or persistent in nature, (ii) can be biologically magnified, (iii) are highly toxic and even lethal at very low concentrations. Various types of production activities in South Africa generate many by-products, which are usually discarded but often turn out to be sources of acute environmental hazards. If not contained and handled appropriately, waste, including HW can cause significant problems. Unattended HW lying around leads to unhygienic conditions resulting in health problems. Increasing population growth, accompanied by rapid urbanization and industrialization, increases the volume of HW generated in the country. Improper waste management is aesthetically unattractive and impacts negatively on tourism by creating blight on South Africa’s beautiful landscape. The aim of the study is to assess how HW is discarded across different land use zones in the Musina Local Municipality in order to reduce and manage the negative impacts that they exert to the environment and human health. The objective was to: (i) analyse the state and management of hazardous waste discarded by beauty salons of the central business district of Musina; (ii) Elucidate the state and management of hazardous waste discarded by households located in the suburbs of Musina; (iii) Document the state and management of hazardous waste discarded by automotive workshop located in the Industrial zone of Musina and (iv) Develop tailor-made recommendations for the safe management of hazardous waste in the town of Musina, Limpopo Province, South Africa The study was conducted in Musina Local Municipality in Limpopo province, South Africa. Musina is the northern town in the Limpopo Province of South Africa. The study sites were divided into three land use zones; central business district (CBD), suburban area, and industrial zone. In terms of methodology observations, a datasheet and a semi-structured questionnaire were used to collect data on HW management across three different land use zones. A total of 73 semi-structured questionnaires (55 in suburban area and 10 in industrial zone and 8 in the Central Business District) were employed to document quantitative and qualitative data. Observations were used to identify the types and document quantity of HW discarded by all participants. The researcher opened the weekly municipal refuse bags that stored discarded products to list and count HW products. The information was captured on a datasheet, which recorded data on type, quantity and separation of hazardous waste from general waste. Data was analysed via descriptive statistics. Results from Central Business District (Salons) shows that nail varnish bottles were the most discarded HW product with 250 discarded per week by all eight salons. Other HW products discarded include artificial nails, hair dye containers, plastic combs, vinyl gloves and disinfectant containers. All salons practice the same disposal method; making use of municipal refuse bags for temporary storage, which is then transported to the municipal landfill site for final disposal. None of the participants separate waste; reasons being lack of awareness of separation management. Shop owners and employees’ attitude towards HW management was neutral while their level of knowledge on the environmental and human health impact was rated low. Seventy-five percent of the respondents were not aware that the products they discard are hazardous. Results from Suburban area (household hazardous waste) shows that home cleaning products were the most discarded Household Hazardous Waste (HHW) product with 237 discarded per week by all 55 sampled households. Other HHW products discarded include personal cleaning products, miscellaneous items, automotive maintenance and gardening products. The 50 households practice the same disposal method; making use of house bin (usually pedal bins). Once the bin is full, they dispose it to the outdoors wheelie bins. The remaining five household dispose of their waste directly to the outdoor bin. None of the participants separated waste; main reasons being lack of awareness of separation management. Participants’ attitude towards HW management was neutral while their level of knowledge on the environmental and human health impact was rated medium. Seventy-three percent of the respondents were aware that the products they discard are hazardous. Results from Industrial Zone (hazardous waste) shows that plastic components were the most discarded hazardous waste (HW) product with 31 discarded per week by all 10 sampled automotive workshops. Other HW products discarded include lead-acid batteries, automotive used oil and paint containers. Automotive workshops practice different storage and disposal method; making use of drums, large containers and old scrap car as a temporary storage place. Once the temporary storage is full, 50% opted for recycling while 30% dispose of their waste to the landfill site; the remaining 20% burn their waste in their premises. A large majority (80%) did not separate their waste; main reasons being a lack of awareness of separation management. Participants’ attitude towards HW management was positive while their level of knowledge on the environmental and human health impact was rated low. Half of the respondents were aware that the products they discard are hazardous. Many studies have looked at the comparison between wastes discarded in the rural versus urban area with little attention on specific enterprises. It is more realistic to consider other enterprises because different activities generated different waste. This study was able to assess how waste is discarded in different enterprises such as salons and automotive workshop with an addition of residential waste. To the best of our knowledge this is the first study of this kind. Future research can look at other enterprises such as HW from restaurant or as far as HW discarded by mining sector. The study recommends that the salon enterprise obtains a HW certificate prior to operating a salon, this will increase awareness and make employees more knowledgeable on issues relating to the management of HW. Most of the wastes discarded by sub-urban area were recyclable materials. The municipality can look into collecting recyclable materials separately and taking it to the recycling facilities. It was shocking to find out that there are automotive industries that burn their waste (without even separating). This poses a serious danger in terms of air pollution and the possibilities of containers exploding; therefore, there is an urgent need to educate people in the automotive industry. Keywords: Hazardous waste, Household Hazardous Waste, Musina, Central Business District
Thesis (M.Sc. (Geography)) -- University of Limpopo, 2021
Keywords: Hazardous waste; Household Hazardous Waste; Musina; Central Business District; Hazardous waste; Pollution; Hazardous waste sites -- Field screening